Eine digitale Transkription des "Deutschen Ptolemaeus'' - Görz, Günther; Lindner, Bettina (Magazin für digitale Editionswissenschaften, 2014)
UnivIS-Import:2015-03-11:Pub.2014.tech.IMMD.lehstu.agdigi.einedi

Frühneuzeitliche "Gesundheitsministerien" : die Aufgaben medizinischer Kollegien am Beispiel des Collegium Medicum Onoldinum - Lindner, Bettina (Jahrbuch des Historischen Vereins für Mittelfranken, 2013)
UnivIS-Import:2015-03-09:Pub.2013.phil.dgeko.LGDSM.frhneu

Historische Einleitung - Lindner, Bettina (Der Deutsche Ptolemaeus, 2008)

Medizinische Gutachten des 17. und 18. Jahrhunderts. Sprachhistorische Untersuchungen zu einer Textsortenklasse. - Lindner, Bettina (De Gruyter, 2017)

Quotations from 17th and 18th Century Medical Case Reports - Lindner, Bettina (The Pragmatics of Quoting Now and Then, 2015)
As recent research shows, 29 % of quotations featured in modern surgical publications are inaccurately quoted, and it is estimated that misquotation in medical literature amounts to 17 % of all quotes (Regier 2010). This is remarkable since quotation is one of the characteristic and often defining features of scientific texts (Jakobs 1999, Gläser 1990). However, to the best of this author’s knowledge, the historical development of quoting in medical contexts has not been investigated at the time of writing, either in linguistics or in the philosophy of language. This diachronic study describes some aspects of the development of quotation forms and functions in Early Modern German scientific medical literature and investigates to what extent modern expectations on quotation can be applied to historical scientific medical literature. The focus is on medical case studies which came into use towards the end of the 17th century. The results are heterogeneous: different forms of quotation were used and the way in which they were reproduced varied, but all in all most medical authors preferred reported speech. It is only when physicians quoted colleagues that varying forms of quotation were utilized, direct speech and reported speech. In general, quotation was not as common in the 17th century as it was in the 18th century, nor was it an obligatory feature of case reports. It may become evident through the discussion of the data that quotation customs only begin to meet modern expectations by the end of the first half of the 18th century, as standard conventions of scientific presentation were not well established prior to this.
Keywords: medico-legal history; medical literature; case reports; quoting authorities

Zur "glücklichen Erreichung jenes gemeinersprieslichen Endzwecks" - Die fränkischen Collegia Medica im Vergleich - Lindner, Bettina (Jahrbuch für fränkische Landesforschung, 2012)